Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1289/ehp.0901602
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Patterns of Ambient Endotoxin Concentrations in Fresno, California

Abstract: BackgroundEndotoxins are found in indoor dust generated by human activity and pets, in soil, and adsorbed onto the surfaces of ambient combustion particles. Endotoxin concentrations have been associated with respiratory symptoms and the risk of atopy and asthma in children.ObjectiveWe characterized the temporal and spatial variability of ambient endotoxin in Fresno/Clovis, California, located in California’s Central Valley, to identify correlates and potential predictors of ambient endotoxin concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 44 publications
9
41
0
Order By: Relevance
“…In the present study, the endotoxin concentrations ranged < LOD to 20.62 EU/m 3 , with an overall mean and median of 2.75 and 1.27 EU/m 3 , respectively. This concentration range is comparable with those reported in other studies that have investigated ambient endotoxin concentrations in various countries (i.e., USA, Germany, Sweden, and Hong Kong) (Mueller-Anneling et al, 2004;Morgenstern et al, 2005;Tager et al, 2010;Nilsson et al, 2011;Cheng et al, 2012). However, the concentration range observed in the present study was lower than those reported in previous studies conducted in occupational settings, wherein the measurements were generally performed at the sources of endotoxins (Su et al, 2002;Madsen and Nielsen, 2010;Rimac et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the present study, the endotoxin concentrations ranged < LOD to 20.62 EU/m 3 , with an overall mean and median of 2.75 and 1.27 EU/m 3 , respectively. This concentration range is comparable with those reported in other studies that have investigated ambient endotoxin concentrations in various countries (i.e., USA, Germany, Sweden, and Hong Kong) (Mueller-Anneling et al, 2004;Morgenstern et al, 2005;Tager et al, 2010;Nilsson et al, 2011;Cheng et al, 2012). However, the concentration range observed in the present study was lower than those reported in previous studies conducted in occupational settings, wherein the measurements were generally performed at the sources of endotoxins (Su et al, 2002;Madsen and Nielsen, 2010;Rimac et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding endotoxins, studies conducted in California, USA, reported spatial variability of endotoxins throughout the study area. Endotoxin concentrations have been associated with agricultural and pastureland areas, particularly in the downwind direction (Mueller-Anneling et al, 2004;Tager et al, 2010). However, a low spatial variability was also reported in a study by Morgenstern et al,(2005), which investigated the spatial distribution of endotoxins in Munich, Germany; this may be due to the similar characteristics of the sampling sites, which were all located in an urban area.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations